The prophet king - Khan, Saniyasnain (Goodword Books Place of publication not identified, 2002)
"The Prophet King" by Saniyasnain Khan is a children's story that narrates the life of Prophet Solomon (Sulaiman), highlighting his wisdom, justice, and deep connection with both people and nature.